2010
DOI: 10.1097/opx.0b013e3181ce5702
|View full text |Cite
|
Sign up to set email alerts
|

Proptosis in Dysthyroid Ophthalmopathy: A Case Series of 10,931 Japanese Cases

Abstract: This study assessed the measurable features of proptosis in Japanese patients with DO and contributes to the understanding by correlating symptoms and signs of DO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 16 publications
3
22
1
Order By: Relevance
“…Lid swelling is observed in 47% of GO patients, with injection and edema of the conjunctiva observed in 32% (29).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lid swelling is observed in 47% of GO patients, with injection and edema of the conjunctiva observed in 32% (29).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The female to male ratio is 4.2 in Swedish patients (31) and 3.9 in Japanese subjects (29). Moreover, the female to male ratio varies according to the severity of ophthalmopathy, being 9.3, 3.2 and 1.4 in patients with mild, moderate and severe ophthalmopathy, respectively (28).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kozaki et al noted clinically significant proptosis (>/=15 mm) in 74.2% of adult patients. The average exophthalmometer reading was 17.2 +/-3.2 mm, with proptosis less pronounced with age [24].…”
Section: Clinical Signmentioning
confidence: 90%
“…Kozaki et al (2010) showed lid retraction in 57.7% of adult patients [24]. Eyelid retraction may be of thyroid hormone excess, an increased stimulation of the eyelid retractors or innervation of the superior rectus/levator muscles and contracture, overactivity of Muller's muscle, contracture of inferior rectus muscle [23,24].…”
Section: Clinical Signmentioning
confidence: 99%